A vinculação entre a dignidade humana e os direitos fundamentais na jurisprudência do Tribunal Constitucional Federal da Alemanha : do processo de elaboração da lei fundamental à análise da recepção e influência de suas decisões na judicatura do Supremo Tribunal Federal - Sandi, Ramon da Silva (2021)
In view of the necessary and urgent protection to the human person after the events of the World War II, the pursuit to ensure that the powers of the future German State were limited and acted in accordance to human dignity and fundamental rights started through the process of elaboration of the Basic Law of Germany. As a result, the Basic Law of Germany (1949) recognized human dignity as an unparalleled function in the constitutional order, binding the legislator and all public authorities to its protection. Based, precisely, on the duties of respect and protection, the Federal Constitutional Court of Germany issued decisions that linked the content of dignity to constitutional principles, but mainly to fundamental rights. In view of the importance of their judgments, many of its decisions and justification were and are still used in the Brazilian legal-constitutional order, mainly in the judicature of the Supreme Federal Court. Thus, seeking to understand, firstly, the meaning of the connection of human dignity and fundamental rights in the process of elaboration of the Basic Law, the objective of this dissertation is to undertake a study on the jurisprudence of the Federal Constitutional Court of Germany and its reception and influence in the judicature of the Federal Supreme Court. The method used was analytical, making use of bibliographic materials of the German and Brazilian doctrine, as well as of the reading and study of the jurisprudence of both courts. The procedural method will be historical-comparative. As for the method of legal interpretation, the exegetic method will be used. It is concluded - also from the reflections made in the process of elaboration of the BL - that the FCC’s jurisprudence, based on dignity and fundamental rights, is developed in order to promote the due protection to each human person, standing out the duties of the State to guarantee an existential minimum that also encompasses a social, cultural and political dimension. With the reception of FCC’s decisions, such development is also perceived in the judicature of the Federal Supreme Court, having as examples, the greater scope of negative and positive protection of dignity, highlighting the use of the formula of the object-man; the free development of personality; the content of the existential minimum and the protection duties of the legislator.